Pengukuran Kinerja PDAM Kabupaten Buleleng dengan Metode Balanced Scorecard - Suryana, I Ketut Artha; Erawati, Ni Made Adi (E-Jurnal Akuntansi, 2013)
Regional-Owned Enterprises, including the Regional Water Company, other than as a source of local revenue also has a function to serve the needs of the community, so it is necessary to measure its performance with a concept that not only consider the financial aspect, but also the non-financial aspects, namely the Balanced Scorecard . This study discussed the performance of the PDAM Buleleng based on the perspectives of the Balanced Scorecard, such as the perspective of the customers, finance, internal business process, and learning and growth. Based on the analysis,  the performance of PDAM Buleleng in the  perspective of customer based on Customer Satisfaction Index showed a very good performance. In the perspective of finance, the analysis based on the leverage ratio and growth rate showed a good performance, while based on the activity and profitability ratios showed a good enough performance. In perspective of internal business process, the analysis based on the Service Cycle Efficiency on the new connection installation process showed a not good enough performance, while the customer complaints handling process showed a good performance. In the perspective of learning and growth, the analysis based on the productivity of the employees showed a good performance, and based on the Employee Satisfaction Index showed a good performance.
Keywords: balanced scorecard; kinerja pada perspektif pelanggan; kinerja pada perspektif keuangan; kinerja pada perspektif proses bisnis internal; kinerja pada perspektif pembelajaran dan pertumbuhan